Molecular influenza surveillance at a tertiary university hospital during four consecutive seasons (2012–2016) in Catalonia, Spain. Issue 18 (24th April 2019) - Andrés, Cristina; Peremiquel-Trillas, Paula; Gimferrer, Laura; Piñana, Maria; Codina, Maria Gema; Rodrigo-Pendás, José Ángel; Campins-Martí, Magda; Carmen Martín, María; Fuentes, Francisco; Rubio, Susana; Pumarola, Tomàs; Antón, Andrés
Highlights: There were shifts in the predominance of influenza types or subtypes. Drifted A(H3N2) strains circulated during the 2014–2015 season and a higher hospitalisation rate was reported. Circulation of B/Vic-like viruses not included in the trivalent vaccine during the 2015–2016 season. Virulence and resistance mutations were detected due to an enhanced surveillance. Virological surveillance should be strengthened in hospital settings. Abstract: Background: Influenza viruses (FLUV) are continuously evolving, which explain the occurrence of seasonal influenza epidemics and the need to review the vaccine strain composition annually. The aim is to describe the genetic diversity and clinical outcomes of FLUV detected at a tertiary university hospital in Barcelona (Spain) during the 2012–2016 seasons. Methods: The detection of FLUV from patients attended at the Emergency Department or admitted to the hospital was performed by either immunofluorescence or PCR-based assays. A specific real-time one-step multiplex RT-PCR was performed for influenza A (FLUAV) subtyping. The complete coding haemagglutinin domain 1 (HA1) and neuraminidase (NA) (2015–2016) protein sequences from a representative sampling were molecular characterised. Results: A total 1774 (66.1%) FLUAV and 910 (33.9%) influenza B (FLUBV) cases were laboratory-confirmed. The hospitalisation rate was different between seasons, being the highest (81.4%) during the 2014–2015 season. FLUV were genetically close to vaccine strains except to the 2014–2015, in which most characterised A(H3N2) viruses belonged to a genetic group different from the vaccine strain. During the 2015–2016 season, B/Victoria-like viruses were the most predominant, but this component was not included in the trivalent vaccine used. Mutations D222G or D222N in HA1-domain were found in 3 A(H1N1)pdm09 strains from ICU-admitted cases. Three A(H1N1)pdm09 strains carried the NA H275Y (2) and S247N (1) mutations, respectively related to resistance or decreased susceptibility to oseltamivir. Conclusions: The circulation of drifted A(H3N2) strains during the 2014–2015 season was related to the high hospitalisation rate due to the mismatch with the vaccine strains. The predominance of a FLUBV lineage not included in the trivalent influenza vaccine during the 2015–2016 season highlights the need to use a tetravalent influenza vaccine. Virological surveillance of viral variants carrying protein changes that alter tropism and susceptibility to antivirals features should be strengthened in hospital settings.